The effect of cultivation technologies on nectar-forming capacity by flowers of the promising varieties of buckwheat - F. Z. Kadyrova; L. R. Kadyrova; G. N. Galiullina (Зерновое хозяйство России)
The article considers the results of study of nectar production by the flowers of hybrids, formed on a basis of fasciated morpho-biotypes of buckwheat. Some of them are considered to be promising in breeding on the increase of nectar productivity by flowers. It has been shown that hydrothermal conditions of vegetation, genotypic features of hybrid populations and sowing rates have a significant effect on the amount of nectar productivity. When the sowing time is shifted to the end of May, sowing with less amount of seeds increases nectar-forming capacity of flowers.